Характеристика технологій вчинення злочинів у кіберпросторі - Самойленко, Олена Анатоліївна; Самойленко, Елена Анатольевна; Samoilenko, Olena A. (My University, 2018)
Стаття присвячена характеристиці технологій вчинення злочинів у кіберпросторі. Виділено сім груп таких технологій. У розгляді кожної технології автором робиться акцент на закономірностях її застосування. Наводяться показові приклади технологій із матеріалів судово-слідчої практики.

Статья посвящена характеристике технологий совершения преступлений в киберпространстве. Выделены семь групп таких технологий. При рассмотрении каждой технологии автором делается акцент на закономерностях ее применения. Приводятся показательные примеры технологий из материалов судебно-следственной практики.

Characteristics of technologies of perfection of crimes in cyber space The article is devoted to the characterization of technologies of committing crimes in cyberspace. Seven groups of such technologies are identified, in particular: 1) technology of illegal enrichment, based on the previous acquisition of personal data / commercial secret of an individual / legal entity by unauthorized interference with the operation of computer equipment; 2) the technology of taking non-cash funds through the use of electronic payment systems based on the previous unauthorized interference with the operation of computer equipment; 3) “espionage” technologies based on previous access to state / commercial secrets by unauthorized interference with the operation of computer equipment; 4) technology of official theft through the use of electronic payment systems, based on unauthorized actions with information, perpetrated by a person who has the right of access to it; 5) technology to conceal the illicit origin of non-cash funds, based on the previous unauthorized interference with the operation of computer equipment; 6) technology of illegal enrichment, based on the previous unauthorized interference with the operation of a computer, computer system, network in order to neutralize intellectual protection means; 7) technology of illegal enrichment by illegal actions with payment cards. When considering each technology, the author focuses on the patterns of its application. Illustrative examples of technology based on forensic practice are given.
Самойленко О. А. Характеристика технологій вчинення злочинів у кіберпросторі / О. А. Самойленко // Судова та слідча практика в Україні. – 2018. – Вип. 7. – С. 64-71.
Keywords: алгоритм; злочинна діяльність; злочин; кіберпростір; несанкціоноване втручання; персональні дані; технологія; алгоритм; преступная деятельность; преступление; киберпространство; несанкционированное вмешательство; персональные данные; технология; algorithm; criminal activity; crime; cyberspace; unauthorized interference; personal data; technology